Elite Colleges and Upward Mobility to Top Jobs and Top Incomes - Zimmerman, Seth D. (American Economic Review, 2019)
This paper asks whether elite colleges help students outside of historically advantaged groups reach top positions in the economy. I combine administrative data on income and leadership teams at publicly traded firms with a regression discontinuity design based on admissions rules at elite business-focused degree programs in Chile. The 1.8 percent of college students admitted to these programs account for 41 percent of leadership positions and 39 percent of top 0.1 percent incomes. Admission raises the number of leadership positions students hold by 44 percent and their probability of attaining a top 0.1 percent income by 51 percent. However, these gains are driven by male applicants from high-tuition private high schools, with zero effects for female students or students from other school types with similar admissions test scores. Admissions effects are equal to 38 percent of the gap in rates of top attainment by gender and 54 percent of the gap by high school background for male students. A difference-in-differences analysis of the rates at which pairs of students lead the same firms suggests that peer ties formed between college classmates from similar backgrounds may play an important role in driving the observed effects. (JEL I23, I26, J16, O15)